Automated identification of moth species - Dhillon, Sarinder Kaur; Leong, Y.M.; Elham, Y.K.; Lim, L.H.S. (2016)
In this paper, Digital Automated Identification System (DAISY) was used to identify species of local moths. 210 species of super family Bombycoidea from Moth of Borneo (Part 3) were trained in DAISY. The overall identification of Moths gave a fairly accurate retrieval, with F1= 0.81.